Are the Yo-Yo intermittent recovery test levels 1 and 2 both useful? Reliability, responsiveness and interchangeability in young soccer players - Fanchini, M.; Castagna, C.; Coutts, A. J.; Schena, F.; McCall, A.; Impellizzeri, F. M. (Journal of Sports Sciences, 2014)
The aim of this study was to compare the reliability, internal responsiveness and interchangeability of the Yo-Yo intermittent recovery test level 1 (YY1), level 2 (YY2) and submaximal YY1 (YY1-sub). Twenty-four young soccer players (age 17 ± 1 years; height 177 ± 7 cm; body mass 68 ± 6 kg) completed each test five times within pre- and in-season; distances covered and heart rates (HRs) were measured. Reliability was expressed as typical error of measurement (TEM) and intraclass correlation coefficient (ICC). Internal responsiveness was determined as effect size (ES) and signal-to-noise ratio (ESTEM). Interchangeability was determined with correlation between training-induced changes. The TEM and ICC for distances in the YY1 and YY2 and for HR in YY1-sub were 7.3% and 0.78, 7.1% and 0.93 and 2.2% and 0.78, respectively. The ESs and ESTEMs were 0.9 and 1.9 for YY1, 0.4 and 1.2 for YY2 and -0.3 and -0.3 for YY1-sub. Correlations between YY1 vs. YY2 and YY1-sub were 0.56 to 0.84 and -0.36 to -0.81, respectively. Correlations between change scores in YY1 vs. YY2 were 0.29 and -0.21 vs. YY1-sub. Peak HR was higher in YY1 vs. YY2. The YY1 and YY2 showed similar reliability; however, they were not interchangeable. The YY1 was more responsive to training compared to YY2 and YY1-sub.